"Nyekah" Ceremony in Hindu Community in Sesetan Village, Denpasar: Ethno-Linguistic Study - I Gusti Putu Cahya Arsya Prastika; I Wayan Budiarta; I Nyoman Muliana (RETORIKA: Jurnal Ilmu Bahasa, 2020)
Culture and language are habitual things that are always done by the generation in a region. This research focused on the study of ethno-linguistic that discovered the grammatical meaning, cultural meaning and symbolic meaning of ‘Nyekah’ ceremony in Sesetan village, Denpasar. This research is an ethno-linguistic study in which the researcher will examine the procession of Nyekah in the perspective of linguistic that is related with culture. The method of data collection used is participatory observation, in-depth interviews, and documentation. There were 22 lingual elements that those data were categorized as elliptical sentences. Those data were analyzed to find the grammatical and cultural meaning. Furthermore, in ‘Nyekah’ ceremony there were 6 symbolic data which were used in the ritual. Every symbol had deep meaning that were related with religion, human life and nature.